Assessing Factors Causing Traffic Accident in Kellem Wollega Zone, Oromia, Ethiopia - et. al., Tarekegn Dinku, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study set out to identify the driver related factors and management status in Kellem Wollega Zone. Both open ended and closed ended questionnaires, and structured interviews were designed to the selected sample population. These target population selected from five different sites of the zone, with 520 samples among this 300 are pedestrians, 170 are drivers and 50 are traffic polices and other related responsible bodies. The driver’s factors include demographic variables, over speed, overloading, drunk driving, over taking without enough space and inexperienced driver. And no enough traffic police distribution, lack of road signs and symbols, lack of creating awareness to community, no joint work with institution (government and non-governmental), lack of commitments’ of managing bodies, and corruption are traffic management status responded by participants. Finally, the researchers recommended to the researchers who are interested in this area to extend the study area and include recording the accident and examining of speed of vehicles using appropriate measures.